Mortgage Liquidity Facilities - Hassler, Olivier; Walley, Simon (World Bank, Washington, DC, 2014)
This note brings together some of the policy lessons learnt in the creation of mortgage liquidity facilities around the world. It looks at the main benefits which can be derived from the creation of a mortgage liquidity facility and the conditions under which they can operate most effectively. The note details some of the pre-conditions necessary for the creation of a liquidity facility. There is summary of some of the key techniques used in obtaining security over the mortgage collateral. Lastly two important aspects which are crucial to building confidence in mortgage liquidity facilities are how they are regulated and their corporate governance. The note brings in relevant examples from liquidity facilities which have been set up as far back as 1987 (Malaysia), from developed countries (France) and from facilities still under discussion (West Africa). Overall the note points to the valuable developmental role that mortgage liquidity facilities can play in nascent mortgage markets as an intermediary between capital markets in the primary mortgage markets. This is especially the case in markets where the mortgage lending infra-structure and environment have not developed sufficiently to allow for other more sophisticated alternatives such as securitization or covered bonds.